Effect of complementary feeding behaviour change communication delivered through community‐level actors on infant growth and morbidity in rural communities of West Gojjam Zone, Northwest Ethiopia: A cluster‐randomized controlled trial - Chalachew Abiyu Ayalew; Tefera Belachew (Wiley, 2021)
Abstract Attaining the recommended level of adequacy of the infants' diet remains a serious challenge in developing countries. On the other hand, the incidence of growth faltering and morbidity increases significantly at 6 months of age when complementary foods are being introduced. This trial aimed to evaluate the effect of complementary feeding behaviour change communication delivered through community‐level actors on infant growth and morbidity. We conducted a cluster‐randomized controlled trial in rural communities of Ethiopia. Trial participants in the intervention clusters (eight clusters) received complementary feeding behaviour change communication for 9 months, whereas those in the control clusters (eight clusters) received only the usual care. A pre‐tested, structured interviewer‐administered questionnaire was used for data collection. Generalized estimating equations regression analyses adjusted for baseline covariates and clustering were used to test the effects of the intervention on infant growth and morbidity. Infants in the intervention group had significantly higher weight gain (MD: 0.46 kg; 95% CI: 0.36-0.56) and length gain (MD: 0.96 cm; 95% CI: 0.56-1.36) as compared with those in the control group. The intervention also significantly reduced the rate of infant stunting by 7.5 percentage points (26.5% vs. 34%, RR = 0.68; 95% CI: 0.47-0.98) and underweight by 8.2 percentage points (17% vs. 25.2%; RR = 0.55; 95% CI: 0.35-0.87). Complementary feeding behaviour change communication delivered through community‐level actors significantly improved infant weight and length gains and reduced the rate of stunting and underweight.